A Theory of Domestic Violence in International Law - Meyersfeld, Bonita (2016)
This thesis is born of the question: why do women suffer domestic violence disproportionately to any other group? Why does it continue, in the same form, with the same degree of pain, without rebate? And, if the same harm occurs over and over again, consistent through generations and uniform across borders, why then has the international community not yet developed effective means to address it? This thesis attempts to find a legal answer. This is prefaced, however, by the acknowledgement that the law is only one tool in an array of mechanisms, such as health, economics, and politics, which, if properly combined, could alleviate the pain and difficulties experienced by many victims of domestic violence. The area of law to which I look is international human rights law. My initial motivation for considering public international law arose from the repetition of similar forms of domestic violence around the globe. All over the world women suffer the same type of violence at the hands of their intimate partners and they endure the same feelings of helplessness and isolation when looking to the state for protection. If such violence is universal, it seems then, so too should be the solution. I propose in this thesis that international law, if properly fashioned, can be used effectively as part of this solution. In particular, I maintain that the authoritative enunciation of a norm against domestic violence in international law can improve the way states address domestic violence. I do not propose that individual abusers should be tried by international law. My focus instead is on the extent to which states fail consistently to alleviate domestic violence. This is important because many legal systems appreciate neither the exigency of extreme forms of domestic violence, nor the extent to which women as a group are disproportionately victims of this violence. The result of this lack of appreciation is an almost universal failure to police, prevent and punish domestic violence effectively.3 Due to the socialized normalcy of domestic violence, very few cases are reported or actually prosecuted. Where prosecutions do proceed, victims will often drop their complaints either because they have reconciled with, or because they fear recrimination from, their abuser. Given the disjuncture between the reality of domestic violence and the inefficacy of many legal systems to address it, a revision of the law vis-à-vis domestic violence is needed. Both national and international legal systems are in need of change. This thesis proposes that the international community should adopt a clear and authoritative articulation of a legal right against extreme and systemic forms of domestic violence and a corresponding duty of states to help remedy such violence. This proposition is made on the basis that international law currently does not contain an effective articulation of this right, and that adopting effective global standards in international law for addressing such violence would help improve state enforcement of this right. Under the current state of international law, it is difficult to convince states to prioritize its resources and infrastructures to protect abused women. Articulating clear and effective global standards in international law for addressing extreme forms of domestic violence would provide an important and practical benchmark against which domestic state legislation could be evaluated and re-shaped. Formulating such global standards could place pressure on states to take basic remedial steps against such violence, such as enacting legislation that allows for restraining orders to be made at the same time as a maintenance order, or creating accessible shelters, which will accommodate the divergent needs of women, including their children